Effect of chain length of short-chain fatty acids on their effect on intracranial pressure in rabbits. Issue 5 (May 1982) - Trauner, Doris A; Adams, Heather
Abstract : The short-chain fatty acids propionic, butyric, valeric, isovaleric and octanoic produced elevations in intracranial pressure during intravenous infusion in rabbits. Serum concentrations of these compounds are elevated in patients with Reye's syndrome, and may contribute to the intracranial pressure elevations found in these patients.